Starting Operating Mode of the Combined Traction Levitation System of the Vehicle Equipped with Magnetic Suspension - A.V. Kireev; G.N. Kononov; A.V. Lebedev (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
The article gives the experimental results of the processes occurring in the combined system of traction and magnetic suspension, which was implemented on the basis of the linear switched reluctance motor. The goal of the research is to examine the possibility to combine the levitation and traction functions within one unit. The full- function physical model of the transport system with the magnetic suspension has been produced for experimental verification of the development concept for the combined system of traction and magnetic suspension. The research tests have been performed at the track structure with the limited length in order to study the processes, occurring in the most complicated start-up mode, when the discrete behavior of current in windings has the disturbance effect on the object levitation. The oscillograms of electromechanical transition processes, showing the mutual influence of traction subsystems and a suspension, are provided. The results of researches have illustrated dramatically that the development concept of the combined system of traction and magnetic suspension, based on the linear switched reluctance motor, is absolutely real. Further researches should be aimed at improving the system characteristics by reducing the mutual influence of levitation and traction processes.